2022
DOI: 10.1111/plb.13475
|View full text |Cite
|
Sign up to set email alerts
|

Response of sugar metabolism in the cotyledons and roots of Ricinus communis subjected to salt stress

Abstract: Ricinus communis is an important oilseed crop worldwide and is also considered one of the best potential plants for salt-affected soil improvement in northeast China. However, little is known about photosynthesis and carbohydrate metabolism in this plant, nor the distribution of carbohydrates in cotyledons and roots under salinity stress.• In the present study, seedling growth, gas exchange parameters (P N , E, g s and C i ), carbohydrate (fructose, sucrose, glucose, soluble sugar and starch) metabolism and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, high salt stress can have an irreversible effect on the growth of most plants. High concentrations of salt ions in plant cells can disrupt the structure and activity of intracellular enzymes, causing metabolic disorders and affecting plant photosynthesis [34], which can cause degradation of photosynthetic products and proteins, leading to a decrease in the content of soluble solids, soluble proteins, soluble sugars, and vitamin C. Eventually, crop quality will be seriously affected under high salt stress [35][36][37][38][39][40]. Our results are strongly consistent with the previous findings by showing a changing trend in the content of soluble solids, sugars, proteins, and vitamin C in harvested 'ice cream' radish fleshy roots irrigated by salt water.…”
Section: Discussionmentioning
confidence: 99%
“…However, high salt stress can have an irreversible effect on the growth of most plants. High concentrations of salt ions in plant cells can disrupt the structure and activity of intracellular enzymes, causing metabolic disorders and affecting plant photosynthesis [34], which can cause degradation of photosynthetic products and proteins, leading to a decrease in the content of soluble solids, soluble proteins, soluble sugars, and vitamin C. Eventually, crop quality will be seriously affected under high salt stress [35][36][37][38][39][40]. Our results are strongly consistent with the previous findings by showing a changing trend in the content of soluble solids, sugars, proteins, and vitamin C in harvested 'ice cream' radish fleshy roots irrigated by salt water.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical to maintain the dynamic balance of sucrose biosynthesis, transportation, and distribution for plant growth 57 , 58 . Previous studies have shown that salt stress increased sucrose content and the activities of sucrose phosphate synthase (SPS) and sucrose synthase (SS) 21 , 59 . In this experiment, salt stress resulted in an increase in sucrose and soluble sugar, and a decrease in fructose content in rice leaves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The sugars produced by starch degradation can act as osmoregulatory substances to improve the ability of cells to absorb water 20 . Research showed that under salt stress, the content of starch and soluble sugars dropped, and the content of fructose and sucrose increased, while the activity of enzymes related to sugar metabolism changed in castor cotyledons 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana , AtPho 1 seems to play a role in abiotic stress rather than in starch degradation 8 . The role of Pho in starch synthesis and decomposition has been widely researched, while the gene family’s action in stress resistance via carbohydrate metabolism is worth further research 8 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Phytohormone signal transduction was also a pathway in regulating the salt tolerance response of Rosa chinensis 19 . Phos play an important role in the synthesis and decomposition of starch, not only related to plant energy metabolism, but also to plant stress resistance 8 , 14 . The role of Phos in combating high temperature and drought treatment in R. chinensis is unclear.…”
Section: Introductionmentioning
confidence: 99%